Pola Pembagian Warisan Masyarakat Dolok Sagala Perspektif Ayat Ahkam - Dini Prawesti; Zainal Arifin Purba (Aksioreligia, 2026)
The distribution of inheritance is one of the provisions of Islamic law that is regulated in detail in the Qur'an. However, in practice, some Muslim communities in Indonesia have not fully implemented these provisions due to the strong influence of local customs and traditions, as is the case in Dolok Sagala Village, Dolok Masihul District. This study aims to identify the inheritance distribution patterns prevailing in the Dolok Sagala Village community and to analyze them from the perspective of tafsir ayat ahkam. This research employs a qualitative approach using a field research method. Data were collected through in-depth interviews with religious leaders, village heads, and community members, supported by a literature review of tafsir ayat ahkam works, particularly Tafsir Ayat al-Ahkam by AsSayis and Ahkam al-Qur'an by Al-Jassas. The findings reveal three inheritance distribution patterns in Dolok Sagala Village: equal distribution (dum-dum kupat), which is the most dominant pattern; distribution based on Islamic inheritance law (faraidh); and non-distribution of inheritance on the grounds of preserving family harmony. From the perspective of ayat ahkam, only the faraidh pattern is in accordance with Islamic law, as the inheritance provisions in the Qur'an are qath'i (definitive) and cannot be replaced by customary considerations or family agreements. This discrepancy is influenced by the strength of local traditions and the limited understanding of the community regarding faraidh law. Therefore, efforts to improve Islamic inheritance law literacy are needed through the active roles of religious leaders, educational institutions, and local governments to achieve justice and legal certainty in inheritance distribution.